A case‐study of land–atmosphere coupling during monsoon onset in northern India. (24th April 2019) - Barton, Emma J.; Taylor, Christopher M.; Parker, Douglas J.; Turner, Andrew G.; Belušić, Danijel; Böing, Steven J.; Brooke, Jennifer K.; Harlow, R. Chawn; Harris, Phil P.; Hunt, Kieran; Jayakumar, A.; Mitra, Ashis K.
Abstract: This article presents a land–atmosphere case‐study for a single day during monsoon onset, incorporating data from a research aircraft, satellite products and model outputs. The unique aircraft observations reveal temperature and humidity contrasts of up to 5 K and 4 g/kg in the planetary boundary layer induced by spatial variations in soil moisture. Both antecedent rain and irrigation were found to be drivers of this atmospheric variability. There is also evidence of soil moisture‐induced mesoscale circulations above some surfaces. This is the first time such responses have been observed in situ over India. Soil moisture‐driven temperature anomalies are larger than those found in previous observational studies in the African Sahel. Moreover, irrigation in the region is extensive, unlike in the Sahel, and has a similar atmospheric effect to antecedent rainfall. This implies that historical changes in irrigation practices are likely to have had an important influence on mesoscale processes within the Indian monsoon. We also examine evidence linking soil moisture and cloud formation. Above wetter soils we observed a suppression of shallow cloud, whilst the initiation of deep convection occurred mostly in areas affected by wet–dry soil moisture boundaries. To investigate the impact of soil moisture heterogeneity on large‐scale wind flow, three model depictions of the day are assessed: the European Centre for Medium‐Range Weather Forecasts ERA‐Interim and ERA5 reanalyses, and a high‐resolution (1.5 km) simulation generated using the Indian National Centre for Medium Range Weather Forecasting regional convection‐permitting Unified Model. We find evidence indicating surface flux uncertainties in the models lead to ∼3.5 hPa anomalies in the monsoon trough. This does affect the simulation of monsoon circulation and rainfall. Better representation of mesoscale land–atmosphere coupling is likely to improve the depiction of convection within weather and climate models over India. Abstract : The first in situ observations of planetary boundary layer responses to antecedent rain and irrigation in India (aircraft). A comparison of three models (ERA‐Interim, ERA5 and NCUM) reveals the influence of surface‐induced temperature gradients on the location and strength of large‐scale shear and confluence associated with the monsoon trough. Our results provide observation and model‐based evidence that soil moisture–atmosphere interactions play an important role in the early phase of the Indian summer monsoon.